Evaluation of Biosurfactant Toxicity Using Phytotoxicity Assay - Tong, Foong Sheng (2017)
The inoculum of Pseudomonas sp. was revived from stock culture in glycerol and inoculate into containing minimal salt BH media supplemented with 1% (v/v) n-hexadecane as sole carbon source. The culture was incubated for 7 days to produce the biosurfactants. The calculated biomass of biosurfactant production per gram (dried weight) of bacterial cells were 15.3 g biosurfactant/g cell biomass. The biosurfactants produced was characterized as glycolipid since positive result was obtained in sugar assay and negative result was obtained in protein assay. The ability of biosurfactant to emulsify the engine oil was found equally strong (p<0.05) as the commercial chemical surfactant, Triton X. Seeds of mung beans and fenugreeks were exposed to 0.6 g/L of biosurfactant to assess the phytotoxicity of biosurfactants. The length of roots and shoots of mung bean and fenugreek exposed to biosurfactant showed no significant differences when compared to seeds exposed to deionized water (negative control), but were 6-8 times longer (p<0.05) compared to roots and shoots exposed to Triton X (positive control). The germination index value of mung bean and fenugreek exposed to biosurfactant was 6 and 8 times respectively higher than seeds exposed to Triton X. Hence, the biosurfactant was found to be non-toxic and exhibit no inhibitory effect on the growth of mung bean and fenugreek. Mung bean was more sensitive to biosurfactant when compared to fenugreek based on the GI value obtained. Mung bean could be a better agent for evaluating the toxicity of other biosurfactant.